HISTORY OF MILITARY STRATEGIC THOUGHT - Petrova, Elitsa Stoyanova (Annals of Spiru Haret University. Economic Series, 2016)
The article presents the origin of the strategy and focuses on the historical development of theories of strategy and strategic management. It presents the fundamental theories of strategy; ancient treatises on strategy; thoughts and practices of European military strategists and the American influence on the strategic thought.